2020
DOI: 10.1111/jcmm.15103
|View full text |Cite
|
Sign up to set email alerts
|

Osthole stimulates bone formation, drives vascularization and retards adipogenesis to alleviate alcohol‐induced osteonecrosis of the femoral head

Abstract: Characteristic pathological changes in osteonecrosis of the femoral head (ONFH) include reduced osteogenic differentiation of bone mesenchymal stem cells (BMSCs), impaired osseous circulation and increased intramedullary adipocytes deposition. Osthole is a bioactive derivative from coumarin with a wide range of pharmacotherapeutic effects. The aim of this study was to unveil the potential protective role of osthole in alcohol‐induced ONFH. In vitro, ethanol (50 mmol/L) remarkably decreased the proliferation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…Initially, we identified that the cell activity and osteogenic differentiation capacity of BMSCs had decreased in ONFH rats. A previous study has reported the decreased osteogenic differentiation and the expand of adipocytes deposition in bone marrow of ONFH 24 . There are many potential capacities in BMSCs such as the promotion of osteogenesis 25 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Initially, we identified that the cell activity and osteogenic differentiation capacity of BMSCs had decreased in ONFH rats. A previous study has reported the decreased osteogenic differentiation and the expand of adipocytes deposition in bone marrow of ONFH 24 . There are many potential capacities in BMSCs such as the promotion of osteogenesis 25 .…”
Section: Discussionmentioning
confidence: 93%
“…A previous study has reported the decreased osteogenic differentiation and the expand of adipocytes deposition in bone marrow of ONFH. 24 There are many potential capacities in BMSCs such as the promotion of osteogenesis. 25 Moreover, BMSCs can be used to treat ONFH in the region of osteonecrosis.…”
Section: Discussionmentioning
confidence: 99%
“…14 Our previous studies have indicated that muscone, cordycepin and osthole have beneficial effects for ONFH. [15][16][17] CPA, also known as chrysophanol and 1,8-dihydroxy-3-methyl-anthraquinone, can be extracted from various herbs, including Rumex crispus, Polygonum multiflorum and Cassia obtusifolia. 18,19 CPA has been revealed to possess many beneficial pharmacological effects, such as lipid regulation, neuroprotection, anti-cancer, anti-inflammation, hepatoprotection and anti-obesity function.…”
mentioning
confidence: 99%
“…To a certain extent, it can explain the efficacy of ESWT in treating BMES caused by trauma in this study. Ethanol can significantly reduce the proliferation and osteogenic differentiation of bone marrow mesenchymal stem cells [ 36 ], which is one of the pathogenesis factors of ONFH. ESWT significantly promoted bone morphogenic protein (BMP)-2, BMP-3, BMP-4, and BMP-7 mRNA expression in the callus [ 5 ], and BMP is essential for fracture healing.…”
Section: Discussionmentioning
confidence: 99%